2014
DOI: 10.1007/s10459-014-9545-1
|View full text |Cite
|
Sign up to set email alerts
|

Learning processes in the professional development of mental health counselors: knowledge restructuring and illness script formation

Abstract: An important part of learning processes in the professional development of counselors is the integration of declarative knowledge and professional experience. It was investigated in-how-far mental health counselors at different levels of expertise (experts, intermediates, novices) differ in their availability of experience-based knowledge structures. Participants were prompted with 20 client problems. They had to explain those problems, the explanations were analyzed using think-aloud protocols. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
0
15
0
2
Order By: Relevance
“…A large body of work has suggested a lack of expertise effects in the mental health domain (for reviews, see Dawes, 1994;Garb, 1989Garb, , 1998Tracey, Wampold, Lichtenberg, & Goodyear, 2014). Although some work has suggested cognitive changes as experience in mental health is gained (Brailey, Vasterling, & Franks, 2001;Marsh & Ahn, 2012;Strasser & Gruber, 2014;Vollmer, Spada, Caspar, & Burri, 2013), there is still compelling evidence that experienced mental health professionals are more similar to laypeople than not in many ways. We have demonstrated that experienced mental health professionals show the same influence of context as laypeople.…”
Section: Limitationsmentioning
confidence: 99%
“…A large body of work has suggested a lack of expertise effects in the mental health domain (for reviews, see Dawes, 1994;Garb, 1989Garb, , 1998Tracey, Wampold, Lichtenberg, & Goodyear, 2014). Although some work has suggested cognitive changes as experience in mental health is gained (Brailey, Vasterling, & Franks, 2001;Marsh & Ahn, 2012;Strasser & Gruber, 2014;Vollmer, Spada, Caspar, & Burri, 2013), there is still compelling evidence that experienced mental health professionals are more similar to laypeople than not in many ways. We have demonstrated that experienced mental health professionals show the same influence of context as laypeople.…”
Section: Limitationsmentioning
confidence: 99%
“…The development of illness script is influenced by the integration of individual knowledge and experience in clinical settings (1,12,13), which is critical for a transition from a novice to an expert (1,12,14). The theoretical process of illness script development includes 4 steps (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…The subjects were asked to think out loud (Ericsson & Simon, 1980, 1984, 1993 and explain the terms which were standardised and closely related to the domain. This method is often used in research into expertise, especially in the above-mentioned studies for recording knowledge formation processes (Henrich & Weinhardt, 2018;Strasser, 2006;Strasser & Gruber, 2015). 2.…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative data material arose from the thinkaloud protocols, which was evaluated with the qualitative content analysis according by Mayring (2015). The resulting audio files were transcribed and content-analysed with MaxQDA, using three categories taken from research into expertise, based on Strasser and Gruber (2015) and Henrich and Weinhardt (2018).…”
Section: Procedures For Data Analysismentioning
confidence: 99%